The Relationship Between Unsafe Action and Unsafe Condition with the Incedent on Workers Accidents in Welding Shop, West Aceh - Susy Sriwahyuni; Darmawan Darmawan; Yolanda Oktaria; Sakinah Sakinah (LPPM of NAROTAMA UNIVERSITY, 2022)
Welding shop is a business place specializing in welding service for various types of metal in various ways ; Manually through electric welding, carbide, Argon, lathe, acetylene, or using the help of robotic or laser welding machines. The work accidents on worker in welding shop is often found.The research problem proposed is what factors are the risk factors for work accidents in welding shop of West Aceh Regency. The research design used cross-sectional method with person correlation analysis. The results of the study found a strong relationship between unsafe acts and work accidents on welding shop workers in West Aceh Regency. The P Value of the variable is 0.000 <0.05, it means there is a moderately strong relationship between unsafe conditions and work accidents for welding shop worker in West Aceh Regency, because the P Value of the variable is 0.023 <0.05. Suggestions for this research is the need to provide education and information about risk factors that can cause work accidents in welding shop workers in West Aceh district.